IPTEKS BAGI MASYARAKAT PERENCANAAN PAJAK JANGKA PENDEK - Mokoginta, Mia Istiana; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2017)
Small business enterprise have a significant contribution for Gross Domestic Product (GDP), however small business enterprise have a lack of manajerial skill, limited funds and marketing. Biji Merah Coffee and Roastery is a small business enteprise at Kota Kotamobagu, Bolaang Mongondow, coffee house that provide Â coffee, chocholate dan green tea. This coffee house has not implement short profit planning for operating activity. Â The aims of this research is to increase financial management of small business enterprise coffee house, particularly to estimate future revenues, costs and profit with Cost Volume Profit (CVP) analysis. Â to plan future levels of operating activity. Method implemented with discourse and trained.